Meningkatkan Kompentensi Pengelola Wisata Desa melalui Penyuluhan Pelayanan Prima - Hermawan, Hary (Jurnal ABDIMAS PARIWISATA, 2020)
Customer satisfaction is the key to winning business competition today, including the tourism business. but in the field there are still many tourism people who still ignore this at this time. A phenomenon that is often encountered is cheating in business, attracting prices too high to achieve big profits in a short time, and much more. Therefore, it is very important to do counseling on how to manage good tourism services with a 5-dimensional approach to excellent service, especially for prospective tourism destinations that will develop. To find out the effectiveness of this program, a test of differences in understanding of participants has been carried out regarding excellent service, before and after counseling is conducted. The test results through different tests showed an increase in participants' understanding of excellent service after counseling.